2015
DOI: 10.1111/1462-2920.12884
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biogeography in the coastal waters of northern Zhejiang, East China Sea is highly controlled by spatially structured environmental gradients

Abstract: The underlying mechanisms of microbial community assembly in connective coastal environments are unclear. The coastal water area of northern Zhejiang, East China Sea, is a complex marine ecosystem with multiple environmental gradients, where the distributions and determinants of bacterioplankton communities remain unclear. We collected surface water samples from 95 sites across eight zones in this area for investigating bacterial community with 16S rRNA gene high-throughput sequencing. Bacterial alphadiversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 73 publications
7
86
0
Order By: Relevance
“…In addition, approximate 10 % variation of the BCCs was constrained by the interaction of geographic distance and seawater variables (Fig. 4), which is in concert with the notion that coastal BCCs is controlled by spatially structured environmental gradient (Wang et al 2015). However, there was still a large proportion (54.5 %) of the variation unexplained by the above selected biogeochemical variables (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…In addition, approximate 10 % variation of the BCCs was constrained by the interaction of geographic distance and seawater variables (Fig. 4), which is in concert with the notion that coastal BCCs is controlled by spatially structured environmental gradient (Wang et al 2015). However, there was still a large proportion (54.5 %) of the variation unexplained by the above selected biogeochemical variables (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…We observed that Cyanobacteria were not dominant in the sediments, with a low average relative abundance (0.011%, data not shown). This could be partly explained by the limited light-permeability of the turbid waters containing a great amount of suspended particles in the study area overall27. Correspondingly, a number of previous works reported that Cyanobacteria were not dominant in the coastal marine sediments9115556.…”
Section: Discussionmentioning
confidence: 85%
“…The coastal area of northern Zhejiang is an interconnected marine ecosystem in the East China Sea that covers ~200 km, primarily comprising Hangzhou Bay, which is highly influenced by discharges from the Qiantang River and industry24; Xiangshan Harbor, a semi-enclosed bay, frequently perturbed by aquaculture25; Sanmen Bay, perturbed by booming fishery26; the Zhoushan Islands, located at the mouth of Hangzhou Bay and acting as barriers from the estuary to the ocean; coastal eastern Xiangshan, covered by fishery hot spots; and the Yushan Islands, serving as a reserve area27. In the present study, we used 16S rRNA gene sequencing and PICRUSt functional prediction to investigate regional variations in the diversity and metabolic functional potential of prokaryotic communities in the surface sediments from above coastal zones to answer three questions: (1) Does geographic distance overwhelm local environmental condition in shaping prokaryotic β-diversity?…”
mentioning
confidence: 99%
“…Pronounced spatial patterns of marine bacterial community composition have been described for estuarine areas that exhibit strong salinity gradients [8,46] as well as oceanic water masses with distinct gradients in salinity or temperature for instance [11,16]. However, as part of a semi-enclosed continental shelf sea the German Bight represents a unique, highly productive coastal environment that is strongly influenced by its intertidal flats, freshwater inflow of rivers and exhibits rather smallscale, highly variable hydrographic properties [3,42].…”
Section: Free-living and Particle-attached Bacterial Communities Are mentioning
confidence: 99%
“…Among these environmental factors, temperature and salinity seem to have largest influence on global bacterial community structure and richness [11,24]. On the other hand microbial communities on microscales [23], within estuaries [46] and along transects of up to 2000 km [8,16] varied in response to organic matter distribution, salinity, temperature, depth, nutrient concentrations and suspended particles for instance. Furthermore, the temporal variation has been extensively studied in various aquatic environments.…”
Section: Introductionmentioning
confidence: 99%